Plant communities differ along socioeconomic gradients in Baltimore, MD, and Washington, D.C. - Rothman, Sarah E.; LaDeau, Shannon L.; Leisnham, Paul T. (Frontiers in Ecology and Evolution, 2026)
Plants on residential urban properties can provide valuable ecosystem services or produce harmful disservices depending on fine-scale characteristics tied to plant species identity, such as growth habit or native status. The composition of plant identities on a given block is often influenced by socioeconomic factors, leading to variable green space function across a city. We surveyed residential plants on Baltimore, MD, and Washington, D.C. blocks, documenting differences in structure, richness, and community composition along an income gradient and between abandoned and neighboring occupied properties. Both canopy and ground vegetation on low-income residential properties covered less area and were more likely to contain non-native species than their higher-income counterparts, with different tree, vine, and non-native communities present. Abandoned properties had more canopy cover and higher tree richness than occupied neighbors but similar community composition including five common vines, four of which were non-native. These differences have important implications for ecosystem services, and such fine-scale knowledge could better inform the management of green space to benefit urban residents.